LEGAL REGULATION OF PROPERTY RELATIONS BETWEEN PARENTS AND CHILDREN IN THE RUSSIAN EMPIRE IN THE EARLY TWENTIETH CENTURY - E. Atarshchikova; E. Ponomarev (Гуманитарные и юридические исследования)
One of the most debated problems in the domestic civil law is the social and legal status of the child in the Russian Empire in the early twentieth century. Russian civil and family legislation is not without flaws, gaps and contradictions, which concerns the topic of this study. This prompted the authors to turn to the analysis of the minor issues of the problem - the legal regulation of parents-children property relations. The relevance of the research topic is predetermined by the huge scientific and practical potential of inheritance of property. The interest in this legal problem relates not only to the history of Russian civil law, but also to the designation of the vector of development of legislation in the XXI century. The national law of the Russian Empire, based on centuries-old traditions, mentality of citizens and the practice developed by the beginning of the twentieth century, made a real attempt to consolidate property relations in the family of parents and children in normative legal acts and articles of laws. The authors of the article pay attention to the difficult law enforcement practice of control over the actual implementation of the current legislation. This can be explained by the speciics of life traditions of Russians, the closeness of family-related relations, which can be attributed to varying degrees to all classes of society. According to the authors, the determining role in the regulation of property relations in the family played a non-normative traditional law, enshrined not in the positive laws of the Russian state, but in the customs existing for centuries, taking into account national, confessional and social characteristics. The novelty of this work is an attempt to introduce new legal structures into scientiic circulation in different branches of modern Russian law. The main conclusion of the authors of the article is that property relations in the modern family of Russian citizens should be more actively regulated by the state. Increasing the role of state power and control over the implementation of speciic legal acts will contribute to the improvement of family relations and strengthen the family of Russians as the basis of modern society in difficult conditions of political and economic instability, the formation of a new state of Russia.